Exploring the Use of Wiki as a Technology Tool to Facilitate Student Engagement in a Business Management Module - Gouws, Gareth (My University, 2016)
The majority of literature supports the idea that student engagement is critical in achieving student throughput rates. This study investigated the function technology serves in meeting the needs of students in a first-year Sport Marketing course. Students’ perception of their level of engagement, pertaining to the learning material of a Business Management module, through the use of a technology tool known as “wiki”, is investigated. The data collection tool was in the form of a questionnaire, and findings indicated students viewed wiki as a successful online tool which promotes content engagement. Findings also suggest wiki promotes collaborative learning, improves overall student participation and cognitive engagement. The study affirms the premise that students enjoy incorporating technology into the classroom, thus affirming the idea that by applying a blended learning approach, millennial students experience and achieve greater learning outcomes.
Keywords: Student engagement; Throughput rates; Teaching technology; collaborative learning; Blended learning